2013
DOI: 10.4103/0973-029x.125178
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric analysis of vascularity in normal buccal mucosa, leukoplakia, and squamous cell carcinoma of buccal mucosa

Abstract: Context:Angiogenesis, the process that leads to the formation of new blood vessels, continues to be a topic of major scientific interest. There is an increasing hope that new discoveries will lead to newer therapies that target angiogenesis as a reliable option for disease therapy.Aims:The objective of this study was to assess the role of vascularity, correlation of morphometric aspects of vascularity, investigate its usefulness in the histopathological classification and prognosis in normal buccal mucosa (NBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
1
10
0
1
Order By: Relevance
“…Angiogenesis is fundamental for the growth of solid tumours. Previous studies have suggested that parameters describing angiogenesis could be used for evaluation of aggressiveness and prognosis of OSCC . However, there exists inconsistent data on the increase in vascularity amongst varying degrees of oral dysplasia and carcinomas and its correlation with VEGF .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiogenesis is fundamental for the growth of solid tumours. Previous studies have suggested that parameters describing angiogenesis could be used for evaluation of aggressiveness and prognosis of OSCC . However, there exists inconsistent data on the increase in vascularity amongst varying degrees of oral dysplasia and carcinomas and its correlation with VEGF .…”
Section: Discussionmentioning
confidence: 99%
“…Shivamallappa et al opined that there exist distinct changes in angiogenesis associated with malignant lesions as compared to the pre‐cancerous stage. However, the drawbacks of these studies were that the samples of dysplasia were not graded as mild, moderate and severe . Tae et al reported no increase of MVD from adjacent normal epithelium to premalignant lesions to cancer but did not classify the premalignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…10 Therefore, the understanding of angiogenesis is critical to comprehend the malignant transformation of epithelial lesions of the oral cavity such as OED or OSCC.…”
mentioning
confidence: 99%
“…Sullivan et al (2015) indicaron que este marcador presenta una alta sensibilidad en la tinción de vasos (100 %). CD-31 es una proteína transmembrana o molécula de adhesión ubicada en las células endoteliales (Moriyama et al, 1997;Pujari et al, 2013;Sullivan et al). Sin embargo, la detección contra CD31 mediante inmunohistoquímica necesita un procedimiento riguroso y altos costos.…”
Section: Introductionunclassified